1999
DOI: 10.1080/14622299050011611
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk and protective factors for adolescent tobacco use

Abstract: Knowledge of risk and protective factors for adolescent tobacco use will lead to the development of improved intervention strategies to reduce/prevent tobacco use. Theory and empirical findings demonstrate the multivariate complexity of the etiology of tobacco use. Sociocultural, social/interpersonal, and intrapersonal factors act through mediated chains of ultimate, distal, and proximal influences. Some influences moderate the effects of others. Once tobacco is used, feedback mechanisms modify prior causes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 17 publications
8
98
0
Order By: Relevance
“…The finding is in line with the empirical work by Leatherdale et al (2005) who reported that the odds of a non-smoker being more likely to be susceptible to smoking is high if he or she attends a school with smokers around, while breaking a school rule (including prohibition of smoking) was less likely to lead to increased susceptibility to smoking; this is also in line with Chen et al (2013) who reported that school environment can cause a school to be a high risk place for smoking initiation. The finding also supports the theory by Flay et al (1999) which posits that environment is one of the factors that influences human behavior. The increase in time spent by adolescents in secondary schools in our schooling system would increase the influence of the school environment on individuals, but with strict enforcement of school rules and the law which prohibits individuals below 18 years old from possessing or using tobacco products may help decrease the number of students who smoke in the school compound.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The finding is in line with the empirical work by Leatherdale et al (2005) who reported that the odds of a non-smoker being more likely to be susceptible to smoking is high if he or she attends a school with smokers around, while breaking a school rule (including prohibition of smoking) was less likely to lead to increased susceptibility to smoking; this is also in line with Chen et al (2013) who reported that school environment can cause a school to be a high risk place for smoking initiation. The finding also supports the theory by Flay et al (1999) which posits that environment is one of the factors that influences human behavior. The increase in time spent by adolescents in secondary schools in our schooling system would increase the influence of the school environment on individuals, but with strict enforcement of school rules and the law which prohibits individuals below 18 years old from possessing or using tobacco products may help decrease the number of students who smoke in the school compound.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies (Biener et al, 1997;Albers et al, 2008) showed that consistent application of a rule or message is crucial if it is to be effective with adolescents. Some studies (Flay et al, 1999;Martinez-Donate, 2009) showed that partial smoking ban has not been effective in influencing children not to initiate smoking. Varying sample size, age groups and sampling methods used in the studies may be other factors which contribute to the contradictory results of this study and those mentioned above (Albers et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, a high level of knowledge about the ill effects of tobacco consumption is not necessarily a predictor of low tobacco consumption prevalence (Flay et al, 1999;Rosendahl et al, 2005). GATS survey in multiple countries has shown that awareness about harmful effects of tobacco smoking is very high.…”
Section: Discussionmentioning
confidence: 99%
“…These protective factors likely operate during adolescence and young adulthood when initiation of use of both alcohol and tobacco is most common. Certain environmental influences during adolescence such as peers, parents, and religious beliefs, may limit both exposure to alcohol and exposure to tobacco during this time in life (Cohen et al, 1994;Flay et al, 1994;Flay et al, 1999). However, longitudinal studies also have shown that there is a bidirectional influence between smoking and alcohol initiation in adolescence that appears to be independent of common potential third factors (Jackson et al, 2002;Wetzels et al, 2003).…”
Section: Smoking Initiationmentioning
confidence: 99%